Morphological characterization of sesame germplasm: Morphological characterization of sesame germplasm - K T RAMYA; J.JAWAHAR LAL; H.H KUMARASWAMY; P RATNAKUMAR (Journal of Oilseeds Research, 2020)
The present study was done to characterize 110 germplasm accessions including 26 released varieties for 30 morphological characters and 10 agronomic characters. The qualitative data of morphological characters was subjected to estimate pair-wise dissimilarity co-efficient. The accessions got classified into 7 clusters. Seeds with brown and black coat colour got grouped exclusively in 3 clusters. An attempt was made to associate qualitative data based clustering to agronomic traits to aid selections in segregating population.